The relation between the capability of the self-care agency and the adherence to the pharmacological and non pharmacological treatment among persons with some coronary illness condition (2010)
The purpose of the study – that is descriptive, transversal and co relational by design – was to explore the relation between the selfcare agency and strict adherence to treatment among 115 intentionally selected patients with coronary illness from a group of coronary patients that went to a cardiology clinic in the city of Ibagué during the last term of 2005. We measured the capability of the agency with the evaluating instrument regarding capabilities, i.e. the "Evaluación de la Capacidad de la Agencia de Autocuidado", validated in its Spanish, and we calculated their adherence to pharmacological and non pharmacological treatment via a scale that corresponds to the resulting adherence and the NOC taxonomy indicators along with the valuation guide. The grading scale translated into Spanish was evaluated for comprehension by a group of nurses with clinical and teaching experiences in the area. The clinical profile of the group consisted of three groups according to the complexity of the treatment regimen: 24, 58, 911 of concurrent drugs and the coronary disease condition: coronary disease with conventional management, coronary disease with interventionist management, and patients with heart failure. Via test such as the Pearson test we were able to confirm the moderately positive relation between the agency's capacity to provide self care and their adherence to pharmacological and non pharmacological treatment. This aspect had been suggested when the study request was filed; i.e that the adherence and the capability of the self care agency are positive behaviors that are present with similar characteristics among persons with coronary illness as those in the selected sample group. We confirmed that the complexity of the therapeutical regime has influence in terms of its adherence, even when in this group it only showed in a slight manner but positively, in concurrence with what we found in other reported studies of the WHO (OMS).